(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
The theory and methodology of physical education constitute a foundational interdisciplinary field within pedagogical and sports sciences, integrating insights from physiology, psychology, biomechanics, and sociology to optimize human motor development, physical fitness, and holistic well-being. This comprehensive review explores the conceptual evolution, core principles, methodological frameworks, and contemporary applications of physical education, emphasizing its role in fostering lifelong physical activity, cognitive enhancement, and social development. Drawing upon historical foundations from ancient civilizations to modern evidence-based practices, the analysis underscores the dynamic interplay between theoretical constructs and practical implementation. Key challenges, including technological integration, inclusivity, and adaptation to diverse educational contexts, are examined alongside emerging trends such as personalized training paradigms and the promotion of health-related outcomes. By synthesizing established knowledge with forward-looking perspectives, this article highlights the critical importance of rigorous, scientifically grounded approaches in physical education for addressing global public health priorities and enhancing educational efficacy.